Exploring self-regulation theory as a mechanism of the effects of psychological contract fulfillment: The role of emotional intelligence - Laulié, Lyonel; Briceño-Jiménez, Gabriel; Henríquez-Gómez, Gisselle (Frontiers in Psychology, 2023)
As self-regulation theory has increasingly been used as a theoretical lens to explain the effects of psychological contract evaluations and employee outcomes, we test whether emotional intelligence (an ability for self-regulation) is a potential moderator of these relationships. More concretely, using a multiple times survey design in an education-based organization with 247 participants, we examined whether emotional intelligence moderates the mediation effect of emotional exhaustion on the relationship between psychological contract fulfillment and turnover intentions. Using a structural equations model (SEM) framework, our results support our hypotheses that individuals with low emotional intelligence do not experience the benefits of having fulfilled psychological contracts. Psychological contract fulfillment significantly reduces the likelihood of emotional exhaustion but only for individuals with high emotional intelligence. Consequently, turnover intentions are lower for emotionally intelligent individuals who experience the fulfillment of psychological contracts. Theoretical and practical implications are discussed. We conclude our study by suggesting that emotional intelligence should be considered as a relevant individual difference in future psychological contract research.